Quantitative estimation of Br, Cl, K and Na in sample blood by NAA - Oliveira, L. C.; Zamboni, C. B.; Mesa, J. (Springer, 2006)
Neutron activation analysis, using Au as flux monitor, was applied to determine the concentrations of Br, Cl, K and Na in blood of healthy male and female blood donors, selected from blood banks and hematological laboratories from different regions of Brazil. The aims of this study were to collect more reference values of the Brazilian population as well as to perform hematological investigations. The advantages as well as the limitations of using this nuclear procedure are discussed.